82.8k views
2 votes
How do I solve this question?

How do I solve this question?-example-1

1 Answer

6 votes

Answer:

m=2 and n=3

Explanation:

Step :-

Given
[ 2 x^(n)y^(2) ]^m = 4 x^6 y^4

using algebraic formula
(a^m)^n= a^(mn)

now


2^(m) x^(mn) y^(2m) = 4x^(6) y^(4)

now equating 'x' powers, we get


x^(mn) = x^(6)


mn=6 ....(1)

now


y^(2m) = y^(4)

Equating 'y' powers ,we get

2 m=4

m=2

substitute m= 2 in equation (1)

we get

2 n=6

n=3

verification:-

substitute m=2 and n=3 , we get


[ 2 x^(n)y^(2) ]^m = 4 x^6 y^4


(2 x^(3) y^2)^2 = 4 x^6 y ^4\\


4 x^6 y^4 = 4 x^6 y^4

both are equating so m= 2 and n=3

User Ryanlahue
by
5.8k points